Orthostatic plate in Intensive Therapy Units of São Paulo city - Luque, Alexandre; Garcia Martins, Camila Gabriela; Siegler Santiago e Silva, Marcele; de Córdoba Lanza, Fernanda; Rodrigues Gazzotti, Mariana (O Mundo da Saúde, 2010)
Immobilization and prolonged internment of the critical patient in Intensive Therapy Units (ITU) may have adverse effects. The orthostatic plate may be a resource for early recovery of functional variables of critical patients in ITU; that therapeutic measure is frequently used in other countries. No data exist in Brazil about the availability of this equipment in ITUs or about its frequency of use. The aim of this study was to investigate the frequency of use of the orthostatic plate in ITUs of São Paulo private, public and non profit hospitals. This is a transversal study using semi-structured questionnaire for data collection. 182 institutions were asked to take part in the evaluation, 70 hospitals were included and 15 (21.42%) of the evaluated hospitals answered the questionnaire; 3 (20%) of them had an orthostatic plate, but no one used it as a routine therapeutic resource in Intensive Therapy Units. Most hospitals do not have the plate; from the 3 hospitals that reported to have the equipment, only one uses the plate in the ITU.